Embracing Multimodal Literacies: Enhancing English Language Teaching in the Digital Age (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the integration of multimodal literacies into English language teaching, acknowledging the diverse modes of representation including text, image, sound, gesture, and spatial arrangement. It discusses the significance of multimodal approaches in catering to varied learning styles, fostering deeper comprehension, and promoting creativity in language learning. Practical strategies for integrating multimodal literacies into the English language classroom are provided, such as analyzing visual texts, creating digital stories, and producing multimedia presentations. The conclusion emphasizes the transformative potential of multimodal literacies in enhancing English language teaching and calls for educators to embrace and implement these approaches to prepare students for communication in the digital age.